Financial crisis and capital structure determinants: a study of Portuguese listed firms - Lisboa, Inês (2018)
Firm’s capital structure is not a new theme but is still relevant in financial literature. This work aims to go a step further, not only because the impact of financial crisis is analyzed, but also because stock repurchase is taken into account. First, the evolution of total, long-term, and short-term debt and loans is analyzed. Then capital structure is regressed against crisis, asset structure, non-debt tax shields, profitability, size, growth, liquidity, cash flow, age, debt serving capacity, own shares, and tax rate. Using an unbalance panel of 53 Portuguese firms from 2003 until 2015, and estimating the models with fixed effects to firms, results suggest that all variables exhibit a significant impact on debt. Although the relationship and significance depend on debt’s proxy used. Results also show that short-term debt is more significant in total debt, and that crisis had a great impact, especially in loans.